The role of perceptions in adoption of cricket farming for improved food security and livelihoods - Charles Adino Ng'ong'a; Kelvin Mashisia Shikuku; Mohammed Hussen Alemu; Evans Manyara Nyakeri; Monica Awuor Ayieko (Journal of Agriculture and Food Research)
This study assesses how perceptions related to insect farming influence the likelihood of cricket farming adoption. Using data from a cross-sectional survey of 892 rural households in western Kenya, we employ a logistic regression for analysis. The model controls for several observable covariates, including age, sex, education, access to credit, livelihood source, distance to nearest market, household size, and land under cultivation. The results show that a positive perception of the benefits and ease of implementing insect farming is associated with a significantly higher likelihood of adopting of cricket farming (p<0.05), whereas a negative perception of its pecuniary and non-pecuniary costs, is associated with a lower likelihood of adoption (p<0.05). These findings suggest that households are less likely to adopt cricket farming if they are uncertain about its benefits or perceive it as difficult to implement. Conversely, when farmers view cricket farming as beneficial and easy to implement, they are more likely to engage in the practice. These insights can inform policy interventions aimed at fostering a favorable attitude toward cricket farming by highlighting both its benefits and technical challenges, thus enabling farmers to make informed decisions.